2018
DOI: 10.4236/ojbd.2018.82005
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Diagnosis of Acute Leukemia and Aberrant Antigen: Sohag University Experience

Abstract: Background: Multiparameter flow cytometry is the most important method for the lineage assignment and maturational analysis of acute leukemias (AL) cells. The multi parametric immunophenotyping analysis allows the detection of aberrant antigen expression and the analysis of heterogeneity and clonality of malignant cells in AL. The aim of the work is to study the immunophenotypes of blasts from patients with AL and determine the frequency of aberrant markers. Subjects and Methods: Retrospective study to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…To the contrary of ours, other studies noted different distribution of the aberrant marker expression, many of them reported that CD7 was the most common lymphoid associated antigen in AML followed by CD19 (16, 27,32,33,36,41,57,58). Others noted that CD19 was the most common expressed lymphoid antigen followed by CD7 (18,53).…”
Section: Aberrant Expression In Aml Patientscontrasting
confidence: 98%
See 2 more Smart Citations
“…To the contrary of ours, other studies noted different distribution of the aberrant marker expression, many of them reported that CD7 was the most common lymphoid associated antigen in AML followed by CD19 (16, 27,32,33,36,41,57,58). Others noted that CD19 was the most common expressed lymphoid antigen followed by CD7 (18,53).…”
Section: Aberrant Expression In Aml Patientscontrasting
confidence: 98%
“…There was a male predominance in our AL patients, which is in accordance with most studies that noted that the males are more affected (27,(31)(32)(33)(34). In our study there was a pediatric predominance in AL, this may be due to that ALL was more common than AML.…”
Section: Monosomysupporting
confidence: 91%
See 1 more Smart Citation
“…In a retrospective analysis of data from 144 patients with AL, it was discovered that 61.8% of patients with AL had AML and that AML-M2 (31.8%) was the most prevalent FAB subtype in the AML group, followed by M4-M5 (27.3%). CD7 was the most frequently expressed lymphoid antigen in AML (25%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when abnormal blasts are present, they tend to keep expressing this antigen in later developmental stages of cell maturation. 4 In adult ALL CD34 expression is associated with poor prognosis, as compared to paediatric ALL. Clinical significance and disease prognosis are dependent on CD34 expression among ALL.…”
Section: Introductionmentioning
confidence: 99%